Estimation of non-point source BOD loading in urban area: A case study in Phetchaburi Municipality, Thailand - Punnakanta, Luepol; Sonchaem, Wimon (Science, Engineering and Health Studies, 2018)
The purpose of this study was to develop the equation for the BOD loading estimation from the nonpoint source wastewater in an urban area. Phetchaburi Municipality area was used as a case study. Here, the nonpoint source wastewater areas can be classified into two groups according to their land uses and runoff coefficients. One is the construction building areas having a runoff coefficient in the range of 0.50-0.90 such as commercial areas, government offices and roads. The other is the natural and agricultural areas having runoff coefficient in the range of 0.03-0.30 such as rice paddies, mixed orchards, forests, marshes and swamps. The amount of storm water passing through each of these non-point sources was the independent variable. X1 was the amount of storm water from construction and buildings areas and X2 was that from the natural and agricultural areas. The average of BOD loading during the dry season used to calculate the BOD loading from the noin-point source wastewater was 208.29 kg/day with the standard deviation at 57.89 kg/day. It was also found that the BOD loading from the non-point source wastewater (Y) and the storm water that flows through the first and the second groups were significantly related. By using the weighted least squares method, the equation was = 0.794X1 - 25.455X2. The coefficient of determination was 36.2% and the sum of squared error was 156.78.